Genomic Landscape of Chinese Clear Cell Renal Cell Carcinoma Patients With Venous Tumor Thrombus Identifies Chromosome 9 and 14 Deletions and Related Immunosuppressive Microenvironment - Niu, Shaoxi; Liu, Kan; Xu, Yong; Peng, Cheng; Yu, Yao; Huang, Qingbo; Wu, Shengpan; Cui, Bo; Huang, Yan; Ma, Xin; Zhang, Xu; Wang, Baojun (Frontiers in Oncology, 2021)
Background Clear cell renal cell carcinoma (ccRCC) with venous tumor thrombus (VTT) is associated with a poor clinical outcome. Although several studies have examined the genomic features of ccRCC, the genetic profile of VTT along with its matched primary tumor has not been fully elucidated. Materials and methods Samples of VTT tissues and matched primary tumor tissues from ccRCC patients (n = 25), as well as primary tumor tissues from patients without VTT (n = 25) were collected and analyzed using whole-exome sequencing. Four additional ccRCC patients who were unfit for surgery were treated with an anti-programmed death receptor-1 (PD-1) monoclonal antibody (Toripalimab, 240 mg, Q3W, IV). Results By comparing the primary kidney tumors from ccRCC patients with or without VTT, a relatively higher prevalence of BAP1 and KDM5C alterations were found in ccRCC patients with VTT, and these alterations were associated with worse overall survival in the kidney renal clear cell carcinoma (KIRC) database. Based on subclone analysis, VTT was predicted to primarily originate directly from the primary renal mass. A significantly higher prevalence of CELSR2 and TET2 alterations were identified in the VTTs compared with the matched primary tumors. An increased prevalence of DNA damage repair genes, especially those involved in homologous recombination repair and non-homologous end joining, was found in ccRCC patients with VTT. Notably, VTT was characterized by the increase incidence of copy number loss in the whole exome (p < 0.05), particularly in the chromosome 9 and 14 regions. Deletion of chromosome 9 and 14 was associated with worse survival, unfavorable clinical features, and the presence of an immunosuppressive microenvironment, which was characterized by higher infiltration of regulatory T cells, follicular helper T cells, and resting mast cells, but lower counts of resting CD4 memory T cells and CD8 positive T cells. A significantly lower count of CD4+ and CD8+ tumor-infiltrated lymphocytes was identified in the VTT samples comparing with matched primary tumor. Of note, three out of the four ccRCC patients with VTT in our cohort who were treated with the anti-PD-1 therapy exhibited remarkable remission in the renal mass but no notable shrinkage in the VTT mass. Conclusion Our study revealed the genetic profile of Chinese ccRCC patients with VTT, and identified multiple features associated with known poor outcomes, including gene alterations and copy number loss. The deletions in chromosomes 9 and 14, and the associated immunosuppressive microenvironment may indicate limited sensitivity to anti-PD-1/PD-L1 monotherapy in VTT.